2023
DOI: 10.1002/ece3.9887
|View full text |Cite
|
Sign up to set email alerts
|

A DNA barcode reference library for CITES listed Malagasy Dalbergia species

Abstract: On Madagascar, the illegal and unsustainable exploitation and illegal international trade of Dalbergia (rosewood) precious woods remain a serious conservation problem.Members of this genus are at high risk of extinction as a consequence of logging, mining, and slash and burn agriculture. Morphological identification of these Malagasy species is difficult in the absence of flowers and fruits, especially in the case of cut trees, sawn wood, and finished product. In this study, we use molecular barcoding to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In the study of Dalbergia species, Yu et al analyzed 8 barcode sequences and their combinations of 9 species of this genus and found that the combined sequences had higher identification power than any single sequence [ 26 ]. Similarly, other researchers also proposed the combined sequence as the DNA barcodes for this genus [ 25 , 40 , 44 ]. However, the combination of sequences as DNA barcodes did not attract much attention in the studies of D. odorifera and D. tonkinensis , and the researchers tested only the identification abilities of single sequences in the studies of the two species [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Dalbergia species, Yu et al analyzed 8 barcode sequences and their combinations of 9 species of this genus and found that the combined sequences had higher identification power than any single sequence [ 26 ]. Similarly, other researchers also proposed the combined sequence as the DNA barcodes for this genus [ 25 , 40 , 44 ]. However, the combination of sequences as DNA barcodes did not attract much attention in the studies of D. odorifera and D. tonkinensis , and the researchers tested only the identification abilities of single sequences in the studies of the two species [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…ITS2 F -GGGGCGGATATTGGCCTCCCCTTG ITS2 R -GACGCTTCTCCAGACTACAAT (Saidon et al, 2023) 3. ITS2 F -ATGCGATACTTGGTGTGAAT ITS2 R -TCCTCCGCTTATTGATATGC (Rakotonirina et al, 2023) 4. ITS2 F -ATGCGATACTTGGTGTGAAT ITS2 R -GACGCTTCTCCAGACTACAT (Nasarodin et al, 2023) 5.…”
Section: Methodsmentioning
confidence: 99%